"Der Balkan" in der Krone: Austria between "frontier Orientalism" and amnesiac nationalism. Issue 6 (17th August 2020) - Karner, Christian
Abstract : This article traces the "silent inscription" of (former) colonial relations in the European integration project to their re-inflection in an EU-sceptical medium. To do so, this contribution draws on a corpus of data comprising news-coverage, commentaries and readers' letters published in Austria's largest newspaper, the Kronen Zeitung, whose reach, influence and leanings are well known. The analysis considers the Krone's representations of, and discursive references to, "the Balkans" during the crises-littered period between 2009 and 2017. For analytical purposes this discussion focuses on a sub-sample of invocations of "the Balkans" in the Krone, which have appeared with growing frequency since 2015. Conceptually, the discourse-analytical notion of the topos, or argumentative structure, and anthropological literature on "identity grammars" inform the analysis. The discussion reveals continuities with Austria's historically long-established representational regimes of South-Eastern Europe and novel discursive features. A contemporary paternalism is shown to re-appropriate the nineteenth-century topos of Austria's alleged "civilizing mission" and what André Gingrich (2005) has described as Central Europe's "frontier Orientalism". Furthermore, preoccupations with "the Balkan-route" and its closure articulate a topos of external threats tied to recent migration flows. The article reflects on an "amnesiac nationalism" and its post-imperial entanglements, which are currently re-shaping the European Union.